Beyond translation into chaos: exploring language movement in the French Caribbean - Cunningham, Catriona (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
As Edwin Gentzler’s latest book (2001) reveals, translation studies (as opposed to translating) is an area that is becoming increasingly relevant to both cultural and literary studies. Developing this point further, Sherry Simon states that, “Increasingly, translation and writing have become a particularly strong form of writing at a time when national cultures have themselves become diverse, inhabited by plurality”(Simon 1999: 72). Or indeed how “Symbolically, translation comes to be the very representation of the play of equivalence and difference in cultural interchange: translation permits communication without eliminating the grounds of specificity” (Simon 1992: 159). Therefore, particularly in postcolonial contexts, where the balance of power hinges on questions of language possession and linguistic insecurities, translation allows this power to be repositioned: it can establish a form of plurality by refusing to allow one language to dominate another. In recent works exploring the complex relationship between postcolonial environments and translation,1 these issues are examined in a worldwide context – writings from Quebec, North Africa, India constitute but a few examples. Yet, Simon also draws our attention to processes of translation that allow each language to maintain its own specific identity. In the French Caribbean, this becomes highly problematic because of the tensions between French – the official language – and Creole – the native spoken language.2 This article will explore the difficulties involved in establishing and maintaining this language specificity and will look at how, and if, French and Creole can ‘translate ’French Caribbean culture.